Working the System: What We’ve Learned About Strengthening Accountability - and Nugent, Sarah (2018)
When designing a new project, how often do we set out to strengthen a particular actor’s or institution’s ability to “hold government to account?” What does that mean exactly? Maybe the better question to ask is: what is the most effective way to strengthen accountability in our development work? And then, what does it look …